2022
DOI: 10.3390/su141912754
|View full text |Cite
|
Sign up to set email alerts
|

Influence of COVID-19 on Environmental Awareness, Sustainable Consumption, and Social Responsibility in Latin American Countries

Abstract: This article aims to investigate the effect that COVID-19 has on environmental awareness, sustainable consumption, and consumer social responsibility. Although some recent research focused on this phenomenon, there are still no studies applied to Latin American consumers. In this study, the data comes from 1624 responses from Latin American consumers who also represent different generations, equitably distributed in 400 from Chile (24.6%), 421 from Colombia (25.9%), 401 from Mexico (24.7%), and 402 from Peru (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 94 publications
2
15
0
1
Order By: Relevance
“…Along the same lines, the hypothesis was confirmed that, in the context of the COVID-19 pandemic, consumer social responsibility (SR) has positively impacted on their environmentally responsible purchasing intention (ERPI). This supports previous research evidence on social responsibility and consumer intent to protect the environment during the COVID-19 pandemic [ 1 , 108 ]. Furthermore, there are studies [ 123 ] that point to the commitment of consumers toward the activities of corporate social responsibility of companies (CSR) and how this contributes to their purchase intention.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Along the same lines, the hypothesis was confirmed that, in the context of the COVID-19 pandemic, consumer social responsibility (SR) has positively impacted on their environmentally responsible purchasing intention (ERPI). This supports previous research evidence on social responsibility and consumer intent to protect the environment during the COVID-19 pandemic [ 1 , 108 ]. Furthermore, there are studies [ 123 ] that point to the commitment of consumers toward the activities of corporate social responsibility of companies (CSR) and how this contributes to their purchase intention.…”
Section: Discussionsupporting
confidence: 90%
“…Second, SEM is a perfect method to test the hypothesis of dependency relationships, correlations and the effects of moderator variables [ 107 ]. Finally, recent studies applied SEM to analyze and demonstrate robustness in measurements and structural evaluation [ 4 , 10 , 108 , 109 ].…”
Section: Methodsmentioning
confidence: 99%
“…With the arrival of the COVID-19 pandemic, several studies have explored its influence on consumers’ sustainable consumption behavior [ 3 , 18 , 25 , 44 , 45 , 46 ]. For instance, Severo et al [ 4 ] found that the COVID-19 pandemic is essential in changing people’s behavior, affecting environmental sustainability and social responsibility.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Notably, the impact of the COVID-19 pandemic had a more significant impact on sustainable consumption fluency, followed by environmental awareness and, to a lesser extent, social responsibility. Valenzuela et al [ 3 ] analyzed the impact of the COVID-19 pandemic on consumer behavior in four Latin American countries and found that consumers reported that their behavior had become more ecologically and socially responsible. In addition, these respondents indicated that they had increased their interest in sustainable consumption and purchasing environmentally friendly products to reduce waste and negative environmental impacts.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation